Guardians of the Galaxy. Vol. 1 - Bendis, Brian Michael (Marvel now!, 2015)
While Star-Lord, Gamora, Drax, Rocket Raccoon, and Groot team up with Iron Man to battle the Badoon for control of Earth, Angela, heaven's most fearsome angel, comes for the Guardians. Then, Captain America, Doctor Strange, the Thing, the Hulk, and other familiar faces join the Guardians in the greatest war the future ever saw.